Heat Transfer in U-Tubes: Simulating the Performance of Delta Winglet Pairs in Laminar and Turbulent Flows - Fotis Naoumis; Harris Linardos; Giouli Mihalakakou; John A. Paravantis; Vassilis Kostopoulos (Energies)
As the environmental crisis intensifies, the demand for energy-efficient systems has never been greater. Vortex generators have emerged as an effective method for enhancing heat transfer within tubes. While extensive research has been conducted on their application in straight tubes, studies focusing on their performance in curved tubes remain limited. This simulation study examined three different arrangements of triangular vortex generators in a common flow-down configuration within a U-turn tube to optimize heat transfer. The analysis conducted under constant wall temperature conditions across a range of Reynolds numbers spans both laminar and turbulent flow regimes to evaluate the broader impacts of vortex generators on flow and thermal fields. The efficiency of each arrangement was evaluated based on the Nusselt number and friction factor. Results show a remarkable increase in the Nusselt number, reaching up to 115% for the configuration with the highest number of vortex generators. However, this enhancement was accompanied by a significant increase in the friction factor, rising by up to 383% at higher Reynolds numbers. Overall, vortex generators demonstrated their highest effectiveness in curved tubes during the laminar-to-turbulent flow transition. In fully turbulent flow, the friction factor increased disproportionately to the modest gains in heat transfer. Despite these limitations, the use of vortex generators in curved tubes offers promising efficiency improvements and merits further exploration.